Retrospective analysis of unstable thoracolumbar fractures treated by postural reduction and posterior short segment pedicle fixation - Kalia, Sandeep; Singh, Jasbir; Parashar, Aakash; Verma, Amit; Sharma, Shalini (International Journal of Research in Orthopaedics, 2019)
Background: For unstable dorslolumbar injuries, the controversy in choosing between long versus short segment posterior fixation continues. Methods: 29 patients (13 males, 16 females) with single level unstable thoracolumbar fracture operated by short segment posterior pedicle screw fixation were evaluated retrospectively in terms of kyphosis correction achieved in immediate post-operative period, loss of kyhposis correction at final follow up and clinical outcome on Denis pain scale and any failure of fixation. Average follow up period was 22.07 months (14-40 months). Results: Average age of patient was 35.7 years (15-50 years). Mode of injury was fall from height in 27 patients and road traffic accident in 2 patients. 12 fractures were at L1, 9 at D12, 6 at L2 and 2 at L3. Neurologically 11 had paraparesis, 4 complete paraplegia and 14 were without any deficit. Pre-operative kyphotic angle was 23.023±11.14 (8-50 degrees) which improved to 7.03±4.69 (0-18) post operatively. Kyphosis at final follow up was 11.759±5.901 (2-25). Loss of kyphosis correction at final follow up was 4.79±2.042 (2-10 degrees). Load sharing classification score (LSC) was 6.89±1.345 (4-9). Denis pain scale at final follow up was p1 in 11 patients, p2 in 15 patients and p3 in 3 patients. There was no case of implant failure and only one case had kyphosis correction loss of 10 degrees. Conclusions: Short segment fixation provides stable fixation with good results and there is no correlation between LSC and fixation failure.